2023
DOI: 10.2147/jhc.s443041
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial Chemoembolization Combined with Tyrosine Kinase Inhibitors Plus Immune Checkpoint Inhibitors for Advanced Hepatocellular Carcinoma: A Propensity Score Matching Analysis

Benjian Gao,
Fengyi Yang,
Dongning Zheng
et al.

Abstract: Purpose This study aimed to explore the clinical efficacy of transarterial chemoembolization (TACE) in combination with tyrosine kinase inhibitors (TKIs) plus immune checkpoint inhibitors (ICIs) (triple therapy) compared to TACE alone (monotherapy) for advanced hepatocellular carcinoma (HCC). Material and Methods Data of consecutive advanced HCC patients receiving triple therapy or monotherapy at our center between January 2019 and December 2022 were collected and retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(37 reference statements)
0
2
0
Order By: Relevance
“… 31–34 Interestingly, we also found that age group is an independent predictor for OS, which we believe to be a novel finding. 35–37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 31–34 Interestingly, we also found that age group is an independent predictor for OS, which we believe to be a novel finding. 35–37 …”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34] Interestingly, we also found that age group is an independent predictor for OS, which we believe to be a novel finding. [35][36][37] Worthy of note, a previous review 38 reported that baseline HBV DNA levels were associated with survival prognosis. High HBV DNA levels may influence the prognosis of HBV-related HCC patients under local and systemic treatment.…”
Section: Discussionmentioning
confidence: 99%